Examining the source of island effects in native speakers and second language learners of English - Aldosari, Saad; Covey, Lauren; Gabriele, Alison (Second language research, 2024)
We investigate sensitivity to island constraints in English native speakers and Najdi Arabic learners of English, examining (1) whether second language (L2) learners whose native language (L1) does not instantiate overt wh-movement are sensitive to island constraints and (2) the source of island effects. Under a grammatical account of islands, these effects arise due to violations of syntactic constraints. Under the resource-limitation account, island effects arise due to processing difficulty. The source of island effects is interesting to examine in L2 learners because it is possible that reduced processing abilities in the L2 may lead to the low acceptance of sentences with island violations simply due to the complexity of the sentences themselves as opposed to an adherence to grammatical constraints. To tease apart these accounts, we followed Sprouse et al. in focusing on individual differences in working memory (WM). We used an acceptability judgment task (AJT) to quantify island sensitivity and an automated operation span task to measure WM. Building on Sprouse et al., the AJT tested four island types, but we made several modifications to the task design to address concerns raised by Hofmeister et al.: the stimuli included a ‘context’ sentence to improve the naturalness of the complex wh-sentences. The stimuli also included complex wh-fillers (e.g. which worker) as opposed to bare fillers (who), as semantically rich wh-phrases have been found to be easier to process. Our results showed that learners, like natives, exhibited island sensitivity, and there was no evidence that individual differences in WM modulated island sensitivity for either natives or learners. Our results are compatible with the grammatical view of island effects and suggest that wh-dependencies in both L1 and L2 grammars are similarly constrained by syntax.